Meningkatkan Akses Pendidikan Masyarakat melalui Workshop Gratis: Program Pengabdian untuk Masyarakat - Valensiana, Brigita Febi; Irbayuni, Sulastri (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Learning is a right for every individual. However, many people are still unable to pursue education to the fullest. The field of information technology is currently in high demand. Yet, many Indonesians cannot study this field due to various reasons, such as financial constraints and limited access. Recognizing this, Hacktiv8, in collaboration with the Semarang Android Developer Centre (SANDEC), has organized a free online workshop event for the community members who wish to learn about information technology but lack adequate resources. Through this program, workshop participants receive basic training in Android development, equipping them with relevant skills to compete in the digital era.